Dampak Perubahan Iklim Terhadap Pola Hujan Dikhususkan Bagi Pertanian Di Pulau Sumatera Dan Kalimantan - Wanny K Adidarma; Lanny Martawati; Syofyan D. M.K; Levina Levina; Oky Subrata (JURNAL TEKNIK HIDRAULIK, 2010)
Identification of climate change impact to the rainfall pattern in Sumatera and Kalimantan becomesinteresting because of its climate variability and nonclimate prediction zone if compared with Java whichhas onlyone type of climatewith nonclimate predictionzone that canbe neglected.Thelimited availabilityof rainfall data causes the approach leads to analyze average rainfall duration in certain threshold.Thedetermination of rainfall duration boundary is based on the Oldeman climate classification for crop andsecond crop, i.e. 100200 mm.Analysis of the trend of average rainfall duration in various thresholds,indicates correlation between length and climate pattern.If compared to the equatorial pattern, themonsoon climate can be classified as robust toward climate change, although the wet season length is muchshorter. In equatorial areas,change of rainfall duration is clearly detected and generally showing a negativetrend oralongerdryseason.